2008
DOI: 10.1177/154405910808700602
|View full text |Cite
|
Sign up to set email alerts
|

Professional Oral Health Care Reduces the Number of Oropharyngeal Bacteria

Abstract: Silent aspiration of oropharyngeal pathogenic organisms is a significant risk factor causing pneumonia in the elderly. We hypothesized that regular oral hygiene care will affect the presence of oropharyngeal bacteria. Professional cleaning of the oral cavity and/or the gargling of a disinfectant liquid solution was performed over a five-month period in three facilities for the dependent elderly. Total oropharyngeal bacteria, streptococci, staphylococci, Candida, Pseudomonas, and black-pigmented Bacteroides spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 15 publications
2
109
1
1
Order By: Relevance
“…It has been suggested that the oropharyngeal bacterial flora is a reservoir for respiratory pathogens, and patients with poor oral hygiene have a higher risk of respiratory disease Scannapieco et al, 1992;Scannapieco and Mylotte, 1996 . It has been also reported that oral health care for elderly patients in nursing homes reduces the incidence of bacterial pneumonia Yoneyama et al, 1996;Yoneyama et al, 1999;Ishikawa et al, 2008 . To date, the standard plate counting SPC method h a s b e e n u s e d a s a c o m m o n m e t h o d f o r t h e quantification of oropharyngeal microflora in our laboratory and others Ishikawa et al, 2008;Hirota et al, 2010 . However, the quantification of oropharyngeal Note concentration determined by the SPC method was determined.…”
mentioning
confidence: 64%
“…It has been suggested that the oropharyngeal bacterial flora is a reservoir for respiratory pathogens, and patients with poor oral hygiene have a higher risk of respiratory disease Scannapieco et al, 1992;Scannapieco and Mylotte, 1996 . It has been also reported that oral health care for elderly patients in nursing homes reduces the incidence of bacterial pneumonia Yoneyama et al, 1996;Yoneyama et al, 1999;Ishikawa et al, 2008 . To date, the standard plate counting SPC method h a s b e e n u s e d a s a c o m m o n m e t h o d f o r t h e quantification of oropharyngeal microflora in our laboratory and others Ishikawa et al, 2008;Hirota et al, 2010 . However, the quantification of oropharyngeal Note concentration determined by the SPC method was determined.…”
mentioning
confidence: 64%
“…Professional oral care decreases the microbial counts of the total oropharynx and can be an important strategy to prevent aspiration pneumonia (Ishikawa et al 2008). In our study, all patients were instructed by either the dentist or the dental hygienist to improve oral hygiene to keep the level of O'Leary plaque control < 20%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research studies indicate that poor oral hygiene correlates with an increase in some systemic diseases such as aspiration pneumonia and cardiovascular disease [1][2][3][4] . Poor oral health is increasingly recognized as a link to other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Ishikawa et al [1] documented that levels of oropharyngeal bacteria decreased or disappeared after consistent professional oral health care, including cleaning of teeth, dentures, tongue, and oral mucous membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation